SCS426 Venice: new apple cultivar with glomerella leaf spot resistance and picking time in March - Denardi,Frederico (2019)
Abstract SCS426 Venice was developed by hybridization between Epagri 404-Imperatriz (♀) and Epagri 406-Baronesa (♂), performed at the Epagri Experimental Station in Caçador, SC, Brazil, in 2001. It requires less winter chilling than ‘Gala’ and ‘Fuji’ traditional clones, whose fruit is picked in March. It is resistant to glomerella leaf spot.